Influence of operating parameters on morphology of laser hardened surfaces - Maharjan, Niroj (2018)
Conventional heat treatment of a component is performed in a furnace whereby the component is continuously heated to a high temperature and quenched to get a hardened material. The furnace heating and tempering process take several hours which is expensive over a long run and less flexible. Laser transformation hardening is an attractive heat treatment technology which can be used to enhance the surface properties of highly stressed components such as cams, gears, and bearings without altering its bulk properties. The highly intense laser beam rapidly heats up the irradiated surface above its austenitization temperature which cools down instantaneously (self-quenching) as the laser moves away from the spot producing a hardened surface. The fast heating and cooling generate a non-equilibrium phase transformation of which very little is understood. An attempt was made to improve the surface properties of steel through solid solution hardening and microstructure refinement using a 250 W fiber laser. To identify the effect of various parameters on laser hardening, scanning conditions such as beam spot size, scan rate, power input, surface condition and overlap ratio were controlled. The change in hardness and morphology of laser treated surface were carefully investigated. The results show the surface hardness increased above 800 HV after laser treatment compared to 260 HV of the as-received specimen. It is found that austenitization has the highest effect on hardness achieved and can be controlled by proper choice of laser parameters and scanning rates.